A potential bioaerosol source from kitchen chimneys in restaurants - Xueyun Geng; Changliang Nie; Dan Li; Mingyu Wang; Yan Wu; Xiaomin Sun; Taicheng An; Maosheng Yao; Jianping Huang; Jianmin Chen (Environment International)
Bioaerosols are ubiquitous and have a substantial impact on the atmosphere and human health. Despite the identification of numerous bioaerosol emission sources, the contribution of anthropogenic sources remains inadequately understood. In kitchens, oil stains accumulated at the vent may discharge microorganisms into the environment with airflow, potentially discharging bioaerosol pollution. This putative anthropogenic source of bioaerosols has been long ignored. To investigated whether kitchen chimneys can be a potential source for bioaerosols, air samples, oil stains from in/out chimneys, and surface sand samples were collected near several commercial restaurants. PCoA showed that sampling sites significantly impacted microbiomes, whereas SourceTracker analysis led to the finding that waste grease significantly contributed to bioaerosol composition. Both findings agree with the kitchen chimney as a source of microbes in bioaerosols in the surrounding environment. Furthermore, despite the low biodiversity, a high proportion of stress-tolerant and potential pathogenic bacteria and fungi were found in residual culinary grease, which may escape into the air causing potential risks to human beings. These results led to the proposal that airborne microbiota can originate from cooking waste grease. Immediate actions should be taken into account to enhance disinfection and sterilization aimed at fume vents.